Cooperation between laccase and glucose oxidase in the oxidation of lignin model compound - Mohamed Yazrul, Mohd Yassin (2016)
Lignin is the second most abundant natural polymer. It has a significant and largely unrealized potential as a source for the sustainable production of fuels high-value chemicals. The oxidative functions of lignin, is a very promising way to go, since it holds the possibilities to yield highly functionalised products that can serve as starting materials for other processes in the chemical and pharmaceutical industries. It can replace fossil-based oil as a renewable feedstock that would bring about socio-economic and environmental benefits to our current economy. Its use and targeted functionalisation within biomass refinery processes, however, still needs to be further explored and developed. Gaining a profound knowledge about the structure of lignin, being able to analyse the most suitable enzymes, and understanding the mechanisms that guide the reactions leading to the oxidative depolymerisation of lignin samples from different renewable sources are key requirements for developing successful lignin product. Therefore, in this study lignin model compound (LMC) will be used as a preliminary study to be able to understand the interaction between the enzymes and lignin. First, the control experiment was conducted by oxidizing 3-ethylbenzothiazoline-6-sulphonic acid (ABTS) in the presence of laccase from trametes versicolor (LTV). This enzyme activity was then compared with the oxidation of ABTS in the presence of LTV and glucose oxidase (GOX). The results obtained from the experiment showed the activity of the enzyme was higher when laccase was in cooperated with glucose oxidase. Finally, the oxidation of ferulic acid as a lignin model compound by the mixture of laccase and glucose oxidase (LTV-GOX) in a range of different concentration was employed. It was expected that aromatic compounds will be produced as a result of the oxidation. Therefore Vanillin was chosen to be quantified. However, none of the samples indicated the presence of vanillin due to certain factors.